Conformational control of Pd2L4 assemblies with unsymmetrical ligands. Issue 3 (4th December 2019) - Lewis, James E. M.; Tarzia, Andrew; White, Andrew J. P.; Jelfs, Kim E.
Abstract : Steric and geometric constraints were used to design unsymmetrical ditopic ligands that form single Pd2 L4 cage isomers with high fidelity. Abstract : With increasing interest in the potential utility of metallo-supramolecular architectures for applications as diverse as catalysis and drug delivery, the ability to develop more complex assemblies is keenly sought after. Despite this, symmetrical ligands have been utilised almost exclusively to simplify the self-assembly process as without a significant driving foa mixture of isomeric products will be obtained. Although a small number of unsymmetrical ligands have been shown to serendipitously form well-defined metallo-supramolecular assemblies, a more systematic study could provide generally applicable information to assist in the design of lower symmetry architectures. Pd2 L4 cages are a popular class of metallo-supramolecular assembly; research seeking to introduce added complexity into their structure to further their functionality has resulted in a handful of examples of heteroleptic structures, whilst the use of unsymmetrical ligands remains underexplored. Herein we show that it is possible to design unsymmetrical ligands in which either steric or geometric constraints, or both, can be incorporated into ligand frameworks to ensure exclusive formation of single isomers of three-dimensional Pd2 L4 metallo-supramolecular assemblies with high fidelity. In this manner it is possible to access Pd2 L4 cage architectures of reduced symmetry, a concept that could allow for the controlled spatial segregation of different functionalities within these systems. The introduction of steric directing groups was also seen to have a profound effect on the cage structures, suggesting that simple ligand modifications could be used to engineer structural properties.